(untitled) (Jahangirnagar University Environmental Bulletin, 2013)
Rajbari district of Bangladesh, have been studied and possible health effect were estimated. The experiment has been done by using gamma ray spectrometry system consisting of a HPGe detector coupled with MCA and associate electronics. The average natural radioactivities of 238U, 232Th and 40K have been measured as 29.03±5.67 Bq/kg, 50.91±10.17 Bq/kg and 535.32±89.19 Bq/kg respectively. To estimate health effect due to the activity of those radionuclides, the radium equivalent activity (Raeq), external hazard index (Hex), absorbed dose rate (D) and effective dose have been calculated and compared to the world average values. The results are also compared with the literature values reported for other regions of the world and found that the soil of the study area are not hazards by the radiation and does not pose any harmful effect to the environment. The outcome of this study may provide valuable information about radiation hazard and also may take part in the monitoring of environmental radioactivity. Jahangirnagar University Environmental Bulletin, Vol.2, 1-8, 2013 DOI: http://dx.doi.org/10.3329/jueb.v2i0.16324